Analisis Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Pengunjung Pulau Angso Duo kota Pariaman - Alfinus Masna; Nini Sumarni (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research is motivated by the many problems that occur on Angso Duo Island, Kota Pariaman, including the quality of services and facilities provided to tourists who visit Angso Duo island, Kota Pariaman, so that many tourists are not satisfied with the services and facilities that tourists get. , this type of research is descriptive using quantitative methods that aim to explain and describe the effect of service quality and facilities on visitor satisfaction on Angso duo Island, Pariaman City. The sample used by researchers in this study was 100 tourists, and the data collection techniques used by researchers were observation and distributing questionnaires to tourists visiting Angso Duo Island, Kota Pariaman. The data analysis technique used is Instrument test, Classical Assumption test, hypothesis testing, multiple regression analysis and the coefficient of determination. The results show that the variable Quality of Service (X!), and Facilities (X2) simultaneously have a significant effect on visitor satisfaction on Angso Duo Island, Kota Pariaman, this is proven with a significant value of 0.00 ≤0.05 based on the partial test showing that : 1 Service Quality Variable has a simultaneous effect on visitor satisfaction on Angso Duo Island, Pariaman City, 2. Facilities Variable has a significant effect on visitor satisfaction on Angso Duo Island, Pariaman City, on the Coefficient of Determination test which shows that the R2 value is 0.363 or 36.3% which shows that the variable Quality of Service and Facilities can explain visitor satisfaction on Angso Duo Island, Kota Pariaman by 36.3% and the remaining 63.7% is explained by other factors.